High performance memristor device from solution processed MnO2 nanowires: Tuning of resistive switching from analog to digital and underlying mechanism - Rajkumar Mandal; Arka Mandal; Nayan Pandit; Rajib Nath; Biswanath Mukherjee (Memories - Materials, Devices, Circuits and Systems)
This study reports the synthesis of manganese dioxide (MnO2) nanowires via the hydrothermal method and the fabrication of high-performance memristor devices using solution-processed MnO2 nanowires. Microstructural characterizations, viz, XRD, SEM, EDAX and XPS of synthesized sample revealed highly crystalline structures of MnO2 nanowires. As synthesized MnO2 nanowires, mixed in different weight percentages with poly(methyl methacrylate) (PMMA) solution were deposited on Al electrode to form thin film memristor devices. Resistive switching with both analog and digital behaviors have been realized in Al/MnO2-PMMA/Al device by controlling the weight percentage (wt %) of MnO2 in the composite. When the MnO2 wt % in the composite was low (PMMA: MnO2 = 1:1), the device exhibited analog type switching, while, the higher concentration of MnO2 produced digital types of switching. The On/Off current ratio of the device increased gradually with increase in MnO2 wt %, reaching the highest switching ratio, ca. 106 and excellent endurance (>104 s) for PMMA:MnO2 = 1:8. Temperature dependent charge transport behavior and impedance spectroscopy was further carried out to explain the underlying resistive switching mechanism of the device.